Localization of brain networks activated by acupuncture at anatomically adjacent acupoints in healthy participants: neuroimaging evidence and implications for migraine and stroke - Zhang, Zhiyang; Ouyang, Xu; Xie, Chaorong; Zeng, Lichuan; Fu, Qixuan; Yan, Qinyi; Wang, Tong; Wang, Xiao; Zhao, Ling (Frontiers in Neuroscience, 2026)
BackgroundNeuroimaging investigations reveal heterogeneous acupuncture-induced brain activation patterns. Integrating acupoint-specific activation patterns into a unified connectomic framework enables systematic elucidation of acupoint-specific therapeutic mechanisms through network-level neural decoding.MethodsThis study integrated functional connectivity network mapping (FCNM) methodology, canonical brain networks, and neurotransmitter distributions to delineate the distinct cerebral activation profiles of ST36 (Zusanli) and GB34 (Yanglingquan), two acupoints with anatomical proximity but divergent therapeutic indications in healthy controls (HCs).ResultsThe neural networks activated by acupuncture at ST36 and GB34 are both composed of widely distributed brain regions. These two acupoints co-activated the somatomotor network, the ventral attention network, and the dorsal attention network. The activation pattern of ST36 additionally emphasizes the visual network, while the activation pattern of GB34 primarily involves subcortical regions. The spatial patterns of activation brain networks of ST36 showed exploratory spatial correlations with the distributions of 6-fluoro-(18F)-L-3,4-dihydroxyphenylalanine (FDOPA), noradrenaline transporter (NET) and vesicular acetylcholine transporter (VAChT) neurotransmitter, while the GB34 were correlated with dopamine D1, dopamine D2, dopamine transporter, FDOPA, NET, N-methyl-D-aspartic acid receptor (NMDA), serotonin transporter (SERT), and VAChT neurotransmitter.ConclusionThis study delineates the distinct physiological mechanisms of ST36 and GB34 from neuroimaging and molecular perspectives. This discovery not only elucidates acupoint effect specificity through brain network organization but also expands our understanding of acupoint therapeutic mechanisms within the framework of systems neuroscience, providing a scientific basis for the precise application of acupuncture in treating diseases.